Studi Komparatif Tentang Pentingnya Aspek Agama sebagai Syarat Pernikahan - Agung Taufik Wahyuda (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
So that in the future the two candidates can live peacefully, eternally, shoulder to shoulder and help each other, living in harmony. One of the considerations recommended by Islam when concluding a marriage is kafa'ah. Ulama have different opinions on this issue and we will discuss it in order to find out the opinions of the ulama and their arguments regarding this issue. This writing uses literature research or library study methods, with the process of collecting, analyzing, interpreting data and conclusions from various books related to the problem discussed. Although there are differences of opinion, the majority of scholars agree that religion should be the main consideration in the Kafa`ah of marriage. Even though Muhammad bin Hasan had a different opinion, he still considered religion in cases of wicked behavior.